2017
DOI: 10.1016/j.molstruc.2016.12.098
|View full text |Cite
|
Sign up to set email alerts
|

Nano cube of CaSnO3: Facile and green co-precipitation synthesis, characterization and photocatalytic degradation of dye

Abstract: In this work, nanocubes of CaSnO3 have been prepared by a simple and green co-precipitation method. In this technique, for preparation of calcium stannate, we have used from a complex structure of calcium as a new precursor and the synthesis of CaSnO3 have been done in water as a green solvent. Using of complexing precursors were created a congestion in reaction medium. Different conditions have been studied in synthetic approaches and optimized the effect of different parameters on the morphology of product s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…With the increase in Sn content, the intensity of diffraction signals attributed to CaCO 3 is weakened, and that of those assigned to Ca 0.15 Zr 0.85 O crystal phase is gradually increased. This is mainly due to the introduced Sn species being converted to amorphous CaSnO 3 through the interaction with Ca [22]. The presence of Sn can also be concluded to promote the formation of Ca a .…”
Section: Sn Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…With the increase in Sn content, the intensity of diffraction signals attributed to CaCO 3 is weakened, and that of those assigned to Ca 0.15 Zr 0.85 O crystal phase is gradually increased. This is mainly due to the introduced Sn species being converted to amorphous CaSnO 3 through the interaction with Ca [22]. The presence of Sn can also be concluded to promote the formation of Ca a .…”
Section: Sn Functionmentioning
confidence: 97%
“…With the increase in Sn content, th intensity of diffraction signals attributed to CaCO3 is weakened, and that of those assigned to Ca0.15Zr0.85O crystal phase is gradually increased. This is mainly due to the introduced Sn species being converted to amorphous CaSnO3 through the interaction with Ca [22] The presence of Sn can also be concluded to promote the formation of Ca0.15Zr0.85O and inhibit the further conversion of Ca0.15Zr0.85O to CaZrO3. The catalytic properties of Ca0.68ZrSnx-M with a different Sn content in BDO dehydra tion (Figure 8) show that both BDO conversion and BTO selectivity first increase and then decrease with an increasing Sn amount, and reach up to the highest values when the Sn/Z molar ratio is 0.28.…”
Section: Sn Functionmentioning
confidence: 99%
“…There-aer, the samples were analyzed with the UV-Vis spectrometer. The percentage of water pollutant photocatalytic degradation was measured as follows, 29,30 where A 0 and A t are the concentrations of the water polluter at 0 and t min, respectively, by a UV-Vis spectrometer (eqn (1)).…”
Section: Photodegradation Of Azo Dyesmentioning
confidence: 99%
“…A degradation mechanism was proposed by the authors. CaSnO 3 was also used for the photodegradation of azo-dyes [60,61]. For instance, Moshtaghi et al [61] synthesized CaSnO 3 nanocubes by co-precipitation and showed a good activity for the degradation of acid brown-14 (77%) and acid blue-92 (67%).…”
Section: [Figura 2: Diagrama De Bandas De Um Semicondutor Com Formaçãmentioning
confidence: 99%
“…CaSnO 3 was also used for the photodegradation of azo-dyes [60,61]. For instance, Moshtaghi et al [61] synthesized CaSnO 3 nanocubes by co-precipitation and showed a good activity for the degradation of acid brown-14 (77%) and acid blue-92 (67%). Lucena et al [60] synthesized CaSnO 3 by the modified-Pechini method and evaluated the photodegradation of the remazol golden yellow (RNL) under UV light at different pH values.…”
Section: [Figura 2: Diagrama De Bandas De Um Semicondutor Com Formaçãmentioning
confidence: 99%